Ionic Liquid Properties From Molten Salts to RTILs - Marcus, Yizhak; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume deals with substances in the liquid state that range from high melting salts, such as calcium fluoride, through slags, such as silicates, down to lower melting salts, such as lithium nitrate, molten hydrated salts, such as magnesium chloride hexahydrate, to room temperature ionic liquids, such as 1,3-dimethylimmidazolium tetraphenylborate. It provides the reader with annotated, critically examined, and compiled data for such materials. The data includes a variety of thermochemical, structural, and transport properties. The book includes correlations of measured properties; these correlations should enable the reader to estimate, on a sound basis, properties for ionic liquids that have not yet been measured.
1. Introduction -- 2. Properties of Ions Constituting the Ionic Liquids -- 3. High Melting Salts -- 4. Network Forming Ionic Liquids -- 5. Low Melting Salts -- 6. Room Temperature Ionic Liquids.
Keywords: Electrochemistry; Environmental chemistry; Electrochemistry; Environmental Chemistry